FAKTOR-FAKTOR YANG BERPENGARUH PADA FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Rembulan Adiluhur Fitriandari, 13.05.52.0073; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aimed to examine and analyze the influence of Corporate Governance (Institutional Ownership, Independent Commissioner, Audit Committee Competence) Liquidity, Leverage and Firm Size of Financial Distress Against the Manufacturing Companies Listed on the Stock Exchange Period 2014-2016. The population in this study are all Manufacturing Companies Listed on the Stock Exchange Period 2014-2016. The sample selection using purposive sampling method. The analytical tool used in this research is multiple logistic regression analysis. The result shows that the Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee, liquidity, leverage and firm size does not have significant impact and Liquidity have a significant negative impact against the Financial Distress.Keywords: Financial Distress, Institutional Ownership, Independent Commissioner, Audit Committee Competence, Liquidity, Leverage and Firm Size